Suppose the sum
n = 1 ∑ ∞ [ H n − ln n − γ − 2 n 1 ]
can be expressed in the form of m 1 ( a − c ln ( k π ) + b γ ) , where a , b , c , and m are positive integers and g cd ( a , b , c , m ) = 1 . Find a + b + c + k + m .
Notation:
γ
≈
0
.
5
7
7
2
denotes the
Euler-Mascheroni constant
.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Did the same way.
another way is to simply write the limit k → ∞ lim n = 1 ∑ k ( H n − ln ( n ) − γ − 1 / 2 n ) = k → ∞ lim ( ( k + 1 ) ( H k + 1 − 1 ) − ln ( Γ ( k + 1 ) ) − γ k − 2 H k ) this can be manipulated into k → ∞ lim ( ( k + 2 1 ) ψ ( k + 1 ) − ln ( Γ ( k + 1 ) ) − k ) + 2 γ we can use stirling approximation ln ( Γ ( k + 1 ) ) ≈ ( k + 2 1 ) ln ( k ) − k + 2 1 ln ( 2 π ) → ( k + 2 1 ) ψ ( k + 1 ) ≈ ( k + 2 1 ) ( 2 k 1 + ln ( k ) ) = 2 1 + 4 k 1 + ( k + 2 1 ) ln ( k ) where the second one is just the derivative of the first one multiplied by ( k + 2 1 ) . plugging this in the limit we will have a lot of cancelation resulting in k → ∞ lim ( 2 1 + 4 k 1 − 2 1 ln ( 2 π ) ) + 2 γ = 2 1 ( 1 − ln ( 2 π ) + γ )
Problem Loading...
Note Loading...
Set Loading...
Since H n − ln n − γ = ∫ n ∞ x 2 x − ⌊ x ⌋ d x we see that H n − ln n − γ − 2 n 1 = ∫ n ∞ x 2 x − ⌊ x ⌋ − 2 1 d x = k = n ∑ ∞ ∫ k k + 1 x 2 x − ⌊ x ⌋ − 2 1 d x = k = n ∑ ∞ ∫ 0 1 ( x + k ) 2 x − 2 1 d x Since each of the integrals ∫ 0 1 ( x + k ) 2 x − 2 1 d x is negative, we can write \[\begin{array} {} S & = \displaystyle \; \sum_{n=1}^\infty \Big(H_n - \ln n - \gamma - \tfrac{1}{2n}\Big) \; = \; \sum_{n=1}^\infty \sum_{k=n}^\infty \int_0^1 \frac{x-\frac12}{(x+k)^2}\,dx \\ & = \displaystyle\; \sum_{k=1}^\infty \sum_{n=1}^k \int_0^1 \frac{x-\frac12}{(x+k)^2}\,dx \; =\; \sum_{k=1}^\infty k \int_0^1 \frac{x-\frac12}{(x+k)^2}\,dx \\ & = \displaystyle \sum_{k=1}^\infty k \int_0^1 \Big( \frac{1}{x+k} - \frac{k+\frac12}{(x+k)^2}\Big)\,dx \; = \; \sum_{k=1}^\infty k \,\Big[\ln(x+k) + \frac{k+\frac12}{x+k}\Big]_0^1 \\ & = \displaystyle \lim_{K \to\infty}\sum_{k=1}^K \Big(k\ln\big(\tfrac{k+1}{k}\big) - \frac{k+\frac12}{k+1}\Big) \; = \; \lim_{K \to \infty}\Big[\ln\Big(\frac{(K+1)^K}{K!}\Big) - K + \tfrac12\big(H_{K+1} - 1\big)\Big] \\ & = \displaystyle \lim_{K \to \infty}\Big[\ln\Big(\frac{(K+1)^{K+\frac12}}{e^K K!}\Big) + \tfrac12\big(H_{K+1} - \ln(K+1) - 1\big)\Big] \end{array} \] A simple application of Stirling's approximation tells us that S = ln ( 2 π e ) + 2 1 ( γ − 1 ) = 2 1 ( 1 + γ − ln ( 2 π ) ) making the answer 1 + 1 + 1 + 2 + 2 = 7 .